Application Potential of CTHRC1 as a Diagnostic and Prognostic Indicator for Colon Adenocarcinoma - Pang, Chen; Wang, Hongwei; Shen, Chengcheng; Liang, Houjie (Frontiers in Molecular Biosciences, 2022)
Colon adenocarcinoma (COAD), ranking third in incidence and second in mortality, is one of the most common cancer types in the world. The initial stages of COAD usually show no obvious clinical symptoms; moreover, effective screening or diagnostic indicators with high sensitivity and specificity are lacking, which often leads to missed treatment opportunities. Collagen triple helix repeat containing 1 (CTHRC1) is a glycosylated protein secreted during tissue repair, which reduces collagen matrix deposition and promotes cell migration. Under physiological conditions, the expression of CTHRC1 is conducive to wound healing; however, the pathological overexpression of CTHRC1 promotes tumour growth and proliferation. In this study, we evaluated the application potential of CTHRC1 as an early diagnosis and prognostic survival monitoring biomarker for COAD in addition to unravelling its molecular mechanism in the development of COAD and exploring new therapeutic targets. Therefore, various tumour databases were used to investigate the expression of CTHRC1 in COAD at the mRNA and protein levels. CTHRC1 expression was found to be significantly increased in COAD, regardless of clinical cancer stage, age, sex or race. Moreover, CTHRC1 expression was significantly correlated with poor prognosis and positively correlated with CD8+ T cell, CD4+ T cell, neutrophil, macrophage and dendritic cell infiltration. The relevant function pathways and neighbouring proteins to CTHRC1 in COAD were identified as ROR2, VAPA, LY6E and several collagen family proteins. Therefore, this study suggests that CTHRC1 is a potential diagnostic and prognostic biomarker for patients with COAD.